Peningkatan Kemampuan Guru Membelajarkan Siswa dalam Mata Pelajaran IPS melalui Pendekatan Daur Belajar - Wasih D.S. (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
This classroom action research was intended to improve teacher’s competence in helping children learn science. Learning-cycle approach was implemented in the third grade of Kepanjenlor IV Elementary School in Blitar. The class teacher graduated from DIII program in Civics and had been teaching science just for one year. The data were collected through observation and interview. The results indicate that the approach improved the teacher’s competence in developing instructional design, which was of very-good category, and in helping children learn science, which was of good category.